Determination of biogas production potential from animal manure and GHG emission abatement in Turkey - Karaca, Cengiz (International Journal of Agricultural and Biological Engineering, 2018)
This study was aimed to determine biogas amount and the energy value which could be made from animal manure in Turkey. For this purpose, biogas potential was calculated with the number of dairy cattle and laying hens taking into consideration, which have high availability manure. Turkey has a total of about 8.9 million dairy cattle and 98 million laying hens. Annual total 92.1 million tons of manure is obtained from these animals. There are 89.2 million tons of cattle manure and 2.9 million tons of laying hens manure. Annual 1.6 billion m3 of biogas can be produced from the usable amount of this manure. The heating value of biogas produced from this manure is about 36.7 PJ. These values can provide 1.1% of Turkey’s annual energy consumption (80.5 Mtoe). The distribution of these calculated data by province was mapped using a GIS Software’s mapping option. When provinces are ranked according to the amount of biogas production, the top 10 are Konya, Erzurum, İzmir, Balıkesir, Kars, Afyon, Diyarbakır, Aydın, Ankara and Ağrı. Furthermore, the greenhouse gas (GHG) emission abatement was calculated for demonstrating the environmental benefits of the biogas production from animal manure. It was determined that the CO2 emission abatement annually ranging between 17.2-25.3 million tons could be provided with the evaluation of biogas potential which was calculated.Keywords: biogas, biogas production potential, animal manure, GHG emission, TurkeyDOI: 10.25165/j.ijabe.20181103.3445Citation: Cengiz K. Determination of biogas production potential from animal manure and GHG emission abatement in Turkey. Int J Agric & Biol Eng, 2018; 11(3): 205–210.